Risk Management and Organizational Performance: New Revision of QMS ISO 9001:2015 - Ahmad, Mohd Akhir; Iteng, Rosman; Md Taib, Che Azlan; Mat Nor, Alias (UUM Press, 2017)
Quality management system (QMS) ISO 9000 is a major contribution to achieving local and global competition in the industry. Applying the principles of quality management system and adoption of risk management strategies can help the organization sustainable in their business. Moreover, identifying at early stage the potential risk can have consequential results such as eliminating defects, reducing cost, meeting customer satisfaction and also promoting organization sustainability. In this study, a model that has tendency on how the risk management in the new revision of quality management system (QMS) ISO 9001:2015 can influence the organizational performance is conceptually proposed.